A New Proposed Design Of A Stream Cipher Algorithm: Modified Grain-128 - Norul Hidayah Lot @ Ahmad Zawawi; Kamaruzzaman Seman; Nurzi Juana Mohd Zaizi (2024)
The objective of this research is to propose a new algorithm based on the existing Grain - 128 stream cipher algorithm. The comparison of Grain - 128 and Modified Grain - 128 will be evaluated by using NIST Statistical Test Suite. The NIST Statistical Test Suite is conducted to determine the randomness of both algorithms. Conclusively, the Modified Grain - 128 is random based on 1% of significance level compared to the Grain - 128 which is not random at the same significance level.